2015
DOI: 10.1177/0194599815596169
|View full text |Cite
|
Sign up to set email alerts
|

Referral Patterns and Positive Airway Pressure Adherence upon Diagnosis of Obstructive Sleep Apnea

Abstract: To our knowledge, this is the first study to define the subsequent management of patients who have failed or refused PAP. Despite the known sequelae of OSA, clinicians are not treating a significant percentage of patients with diagnosed OSA. Those who fail to tolerate PAP therapy are unlikely to be referred for additional treatment. Therapies other than PAP may be warranted in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It is not uncommon to see patients, even those with severe obstructive sleep apnea syndrome and symptoms, who reject any treatment for various reasons, including low disease severity perception, the opinion that being connected to a medical device is unacceptable, self‐esteem in terms of their relationship with a partner, patient impression that sleepiness is due to overwork, early awakening or shift work, invasive nature of the treatment (surgery), and the economic cost of OAs. In a recent publication, nearly half (46%) of all patients with diagnosed OSA were not being actively treated for this condition. The groups were matched by age, sex, body mass index (BMI), and AHI.…”
Section: Methodsmentioning
confidence: 99%
“…It is not uncommon to see patients, even those with severe obstructive sleep apnea syndrome and symptoms, who reject any treatment for various reasons, including low disease severity perception, the opinion that being connected to a medical device is unacceptable, self‐esteem in terms of their relationship with a partner, patient impression that sleepiness is due to overwork, early awakening or shift work, invasive nature of the treatment (surgery), and the economic cost of OAs. In a recent publication, nearly half (46%) of all patients with diagnosed OSA were not being actively treated for this condition. The groups were matched by age, sex, body mass index (BMI), and AHI.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown that perceived benefit of therapy, 20,45,46 perceived self-efficacy, 20,47 patient education, 48 and structure in the home 46 are important predictors of discontinuation of PAP therapy. Another limitation is that the nonadherence rate measured in this study is limited to patients whose provider prescribed and submitted sleep preauthorization; the patients whose providers did not order a test or therapy knowing that the patient would not use PAP 20,22 were not included, so missed opportunities for OSA treatment benefit may have been underestimated. An additional limitation is that the study assumes that testing and treatment are appropriate after it is prescribed by the practitioner and preauthorized by the sleep management program; it does not take into account shared decision-making processes (or lack thereof) with the patient, particularly in more mild cases of OSA, or other valid reasons for patients not to proceed with testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among those in whom OSA has been diagnosed, 46% to 55% either refuse PAP therapy outright or do not adhere to treatment. 21,22 In late 2013, an internal report within a large commercial health insurer revealed a substantial gap between the number of preauthorizations for sleep services (sleep apnea testing and PAP treatment initiation) and the actual number of services for which a billing claim was submitted. That is, patients did not undergo diagnostic testing or initiate treatment even though the service had been prescribed by a physician and approved by the insurer as clinically appropriate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For many patients, a diagnosis of obstructive sleep apnea (OSA) results in a single treatment option of positive airway pressure (PAP) therapy, but PAP is not always accepted and long-term adherence to PAP is not achieved by a substantial percentage of patients. 1 The PAP-or-none approach has been gradually replaced by personalized treatment that includes oral appliances, modern upper airway surgery, positioning devices, weight loss, and-most recently-implantable hypoglossal neurostimulation (HGNS). To help match treatment modalities to patients, various phenotypes and endotypes such as loop gain, arousal threshold and anatomic burden have been identified but application of these measures is hampered by methodological complexity.…”
mentioning
confidence: 99%